Alfalfa forage yield, milk yield, and nutritive value under intensive cutting. Issue 2 (28th April 2022) - Eckberg, James O.; Wells, Samantha S.; Jungers, Jacob M.; Lamb, JoAnn F. S.; Sheaffer, Craig C.
Abstract: Forage yield, nutritive value, and stand persistence are key metrics in alfalfa ( Medicago sativa L.) management. The combination of cultivar improvement, longer growing seasons in the Midwest, and trends of shorter alfalfa rotations offer opportunity to reevaluate the effects of increasing cutting frequency (CF) on these metrics. We evaluated forage yield, nutritive value, milk production, and persistence of eight alfalfa entries with fall dormancy (FD) ranging from two (FD2) to five (FD5) under CF of four (CF4), five (CF5), or six (CF6) annual cuts during two production years in two environments in the upper midwestern United States. Nutritive value and milk kg –1 alfalfa increased with increased CF and differed among alfalfa entries. Cutting frequency and alfalfa entry interactively influenced forage yield and milk production ha –1 yet optimal CF depended on environment. At one environment, increasing CF from CF4 to CF5 and from CF5 to CF6 caused a 5 and 29% decrease in milk ha –1, respectively. At another environment, CF5 had about 16% greater milk production than CF4 and CF6. The CF6 reduced persistence of 3rd‐year stand density with the effects especially severe for some entries. Alfalfa entry FD was not correlated to forage yield or persistence, but an entry with FD5 was consistently among those with the greatest in forage and milk yield ha –1 at CF5 and CF6. These results suggest that intensifying CF from four to five harvests per season of some cultivars can boost yield and nutritive value without negative effects on stand persistence in some environments. Core Ideas: Alfalfa forage quality increased with increased cutting frequency. Alfalfa cultivars were affected differently across cutting frequencies. Alfalfa fall dormancy was not correlated to forage yield or persistence across cuttings. Intensifying cutting frequency from four to five harvests per season can increase yield.